2003
DOI: 10.1046/j.1468-2982.2003.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitric Oxide Synthase Inhibition on Histamine Induced Headache and Arterial Dilatation in Migraineurs

Abstract: We have previously proposed that histamine causes migraine via increased NO production. To test this hypothesis, we here examined if the NOS inhibitor, L-NG methylarginine hydrochloride (L-NMMA:546C88), could block or attenuate histamine induced migraine attacks and responses of the middle cerebral, temporal and radial arteries. In a double blind crossover design 12 patients were randomized to receive pretreatment with L-NMMA (6 mg/kg) or placebo i.v. over 15 min followed on both study days by histamine (0.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 32 publications
(63 reference statements)
3
57
0
1
Order By: Relevance
“…In a recent study a decrease in blood speed in the middle cerebral artery, together with vasodilatation in the temporal and radial arteries, was found after histamine infusion. 26 This effect is compatible with the decreased retinal blood speed and increased vessel diameters found in retinal branch veins in this study.…”
Section: Discussionsupporting
confidence: 90%
“…In a recent study a decrease in blood speed in the middle cerebral artery, together with vasodilatation in the temporal and radial arteries, was found after histamine infusion. 26 This effect is compatible with the decreased retinal blood speed and increased vessel diameters found in retinal branch veins in this study.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand several studies demonstrated the key role of inflammatory cytokines in pathophysiology of migraine. These studies showed that serum level of inflammatory cytokines such as IL-1beta and TNF-α and also NO was higher in patients with migraine compared to healthy controls [4,22]. Furthermore, migraine could be considered as a vascular disease and PTX3 like CRP, is independently associated with the risk of developing vascular events [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…15 Similarly, Lassen et al 16 have reported that L-NMMA produced: 1) a 20% increase in blood pressure with a concomitant 24% decrease in heart rate at the maximal dose; 2) a 6.8% decrease in brain blood flow; and 3) no effect on acetazolamide-induced increase in cerebral blood flow. These results suggest that there is no basal NO tone in human cerebral arteries, but that there is a mild dilator tone in cerebral (and systemic) arterioles regulating blood flow and blood pressure.…”
Section: Effect Of No In the Cerebral And Extracerebral Circulationsmentioning
confidence: 93%